Photoactivatable CO release from engineered protein crystals to modulate NF-κB activation. Issue 24 (4th March 2016) - Tabe, Hiroyasu; Shimoi, Takuya; Boudes, Marion; Abe, Satoshi; Coulibaly, Fasséli; Kitagawa, Susumu; Mori, Hajime; Ueno, Takafumi
Abstract : Photoactivatable CO releasing materials were developed by immobilization of Mn carbonyl complexes in polyhedral crystals. Abstract : Photoactivatable CO releasing protein crystals were developed by immobilization of Mn carbonyl complexes in polyhedral crystals, which are spontaneously formed in insect cells. The photoactivatable CO release from the engineered protein crystals activates nuclear factor kappa B (NF-κB) upon stimulation by visible light irradiation with suppression of cytotoxicity of the Mn complex.